ANALYTICAL STUDY OF AWARENESS OF SC/ST STUDENTS IN THE CONTEXT OF NEW NATIONAL EDUCATION POLICY-2020 - Jaimini, Hemlata; Mishra, Poonam (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The objective of this study is to study the awareness of Scheduled Caste and Scheduled Tribe students towards National Education Policy 2020 in the context of the faculty. Survey method was used in this study. A total of 612 graduate level students of Dausa district have been selected for the sample. Data were collected through self-made instrument and mean, standard deviation and CR test statistics were used for analysis. After analysis, it was found in the result that there is no significant difference in the awareness of National Education Policy 2020 of Scheduled Caste and Scheduled Tribe students of Arts, Science and Commerce Faculty of graduation level studying in government and private colleges.